2007
DOI: 10.1097/01.ccm.0000281450.01881.d8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory weakness is associated with limb weakness and delayed weaning in critical illness*

Abstract: Respiratory and limb muscle strength are both altered after 1 wk of mechanical ventilation. Respiratory muscle weakness is associated with delayed extubation and prolonged ventilation. In our study, septic shock is a contributor to respiratory weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
359
4
60

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 483 publications
(432 citation statements)
references
References 38 publications
9
359
4
60
Order By: Relevance
“…Bailey et al (2007) stated that patients who received MV for a period longer than four days were at considerable risk of such debilitation. Prolonged MV has been defined by some as >48 hours and by others as ≥7 days (De Jonghe et al 2007;Chang et al 2005). The duration of LOS reported in this study was substan tially longer than that reported by some authors (Orwelius et Subjects were found to experience problems in all five items of the EQ 5D at six months with some reporting extreme problems in the pain/discomfort and anxiety/depression items.…”
Section: Discussioncontrasting
confidence: 53%
“…Bailey et al (2007) stated that patients who received MV for a period longer than four days were at considerable risk of such debilitation. Prolonged MV has been defined by some as >48 hours and by others as ≥7 days (De Jonghe et al 2007;Chang et al 2005). The duration of LOS reported in this study was substan tially longer than that reported by some authors (Orwelius et Subjects were found to experience problems in all five items of the EQ 5D at six months with some reporting extreme problems in the pain/discomfort and anxiety/depression items.…”
Section: Discussioncontrasting
confidence: 53%
“…After prolonged bed rest, PMV patients may suffer from respiratory muscle weakness, limb muscle atrophy, and decreased ability to perform activities of daily living (ADL). 2 The complications of PMV, such as barotrauma and/or ventilator-induced diaphragm dysfunction can also further impair pulmonary mechanics. These factors together may lead to increased mortality rate, MV weaning failure rate, hospital stay, and impaired physical functional status in the PMV population.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who required at least mechanical ventilation were screened daily for awakening and comprehension using five simple verbal commands as previously described [13,14]. Patients were enrolled in the study and hormonal assays were performed on the first day when awakening and comprehension were satisfactory (day 1).…”
Section: Methodsmentioning
confidence: 99%